Formulasi Hukum Islam; Suatu Kajian Implikasi Lafaz Wadih dan Mubham - Siregar, Fatahuddin Aziz (IAIN Padangsidimpuan, 2018)
Strengthening the understanding of the verses of the Qur'anic verses and the Sunnah feels so important that the legal products produced reflect the true will of the Shari'a, not based on the power of logic alone. There is Lafaz wadih, namely lafaz which is presented in a clear form consisting of various levels, namely zahir, nas, mufassar, and muhkam. Lafaz Zahir and Nas are lafaz that are bright enough but contain several possible meanings, so it needs to be understood by looking at other factors. While mufassar and muhkam do not need factors outside the text to be accurately understood. there is a vague lafaz (mubham), so to just understand it requires a factor outside it. For categories that are fairly clear this does not need to be explored further, it is enough to do it based on the clarity of its meaning. As for what is vaguely presented, an in-depth study is needed to arrive at the right understanding. However, if it is too vague, a mujtahid does not need to force himself to look for food and condemn the law of the lafaz. And indeed there is no need to gain understanding from this type of text, because in general it is not part of the practical life of the law.